Konsep Corporeta Social Responsibility Pegadaian Syariah Dalam Membantu Kemaslahatan Umat Islam - Mujibno Mujibno; Muhammad Samsul Solihin Saleh (Dirosat : Journal of Islamic Studies, 2020)
Social inequalities often occur among people, differences in income, employment and the needs of each community are different factors that differentiate. Corporate social responsibility is one of the social responsibilities in giving a little or even a lot to improve the welfare of the surrounding community. The existence of Corporate social responsibility can have a positive impact on society and the environment. PT. Sharia pawnshops are present in the midst of Indonesian society with the slogan "overcoming problems without problems" is very concerned about social image. CSR itself arises as a result of the public's distrust of the company. There are various kinds of problems that underlie the emergence of CSR such as industrial dehumanization, equalization of public rights, aquariumization of the industrial world and feminization of the world of work. So this CSR is here to provide solutions to problems faced by society and can build a good image for the company. In order for research to produce good knowledge, the method used is a qualitative field research approach. Interview, observation and documentation methods are used to obtain accurate facts. The results of this study, Corporate social responsibility carried out by PT. The Prenduan Branch Sharia Pawnshop has been well implemented. CSR PT. The Prenduan Branch Sharia Pawnshop started in 2018 and continues to this day. The assistance distributed by PT. The Prenduan Branch Sharia Pegadaian is in the form of funds or goods and is distributed without expecting anything in return for the funds provided. PT. CSR Implementation Mechanism. Sharia pawnshops can be done either by submitting proposals or initiatives from companies that need them.